School Community Disaster Resilience: Promoting Geological Disaster Preparedness among Early Childhood Education Teachers - Rahma, Aldila; Rizkiyani, Fanny; Sari, Dianti Yunia; Palupi, Indriati Retno (Universitas Islam Negeri Raden Intan Lampung, 2024)
Preparedness of all components of the school community, including teachers, is essential to build a school's resilience to disasters. This study aims to: (1) examine the geological disaster preparedness level of Early Childhood Education (ECE) teachers in Cisompet District, Garut Regency, and (2) investigate the effectiveness of education on geological disaster preparedness for ECE teachers. This descriptive quantitative study involved 86 ECE teachers recruited using convenient sampling. Data collection was carried out using a pre-test and post-test questionnaire. The results revealed that the teachers' geological disaster preparedness index was 68.94 (ready), which comprised parameters of knowledge and attitudes, emergency response plans, disaster warning systems, and resource mobilization. A geological disaster preparedness education program was conducted for ECE teachers, covering types of geological disasters, potential disasters in Cisompet District, and the establishment of disaster-safe schools. Based on the increase in the percentage of correct answers between the pre-test and post-test, the geological disaster preparedness education for ECE teachers was deemed relatively effective. However, the study found that there is no disaster warning system in either schools or community areas, despite the high disaster risk index. Follow-up activities, particularly through hands-on practice such as disaster evacuation simulations, formulating school disaster contingency plans, and developing learning innovations with disaster content for young children, are still needed.